2020
DOI: 10.1155/2020/4181850
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Global Multidisciplinary Supportive and Educational Intervention in Thermal Resort on Anthropometric and Biological Parameters, and the Disease-Free Survival after Breast Cancer Treatment Completion (PACThe)

Abstract: A growing knowledge highlights the strong benefit of regular physical activity in the management of breast cancer patients, but few studies have considered biological parameters in their outcomes. In the prospective randomised trial after breast cancer treatment completion “PACThe,” we determined the effects of physical activity and nutritional intervention on the biological and anthropometric status of patients after one year of follow-up, and clarified the link between biomarkers at allocation and disease-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Several biomarkers were investigated in the DIANA-5 study by Berrino and colleagues [23]. Vasson and colleagues [24] reported baseline biomarker data from the PACThe study. The WHEL study reported on circulating biomarkers in Emond et al [25], Al-Delaimy et al [26] and Villaseñor et al [27].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several biomarkers were investigated in the DIANA-5 study by Berrino and colleagues [23]. Vasson and colleagues [24] reported baseline biomarker data from the PACThe study. The WHEL study reported on circulating biomarkers in Emond et al [25], Al-Delaimy et al [26] and Villaseñor et al [27].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A complete list of studies with their main characteristics and investigated biomarkers is provided in Table 3. DIANA-2 [20][21][22] and WHEL [25][26][27] consisted of healthy diet interventions, while DIANA-5 [23], and PACThe [24] included both diet and exercise programs. Biomarkers in these studies were measured before lifestyle interventions were implemented.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations